2019
DOI: 10.1016/j.molp.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

PBS3 and EPS1 Complete Salicylic Acid Biosynthesis from Isochorismate in Arabidopsis

Abstract: Salicylic acid (SA) is an important phytohormone mediating both local and systemic defense responses in plants. Despite over half a century of research, how plants biosynthesize SA remains unresolved. In Arabidopsis, a major part of SA is derived from isochorismate, a key intermediate produced by the isochorismate synthase, which is reminiscent of SA biosynthesis in bacteria. Whereas bacteria employ an isochorismate pyruvate lyase (IPL) that catalyzes the turnover of isochorismate to pyruvate and SA, plants do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
139
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(142 citation statements)
references
References 47 publications
0
139
0
3
Order By: Relevance
“…Pathogen-induced SA accumulation is required for plant immunity, and one major pathway of SA biosynthesis is via isochorismate (IC) (Dempsey et al, 2011). The IC pathway involves several enzymes that are required for the key catalytic steps, and encoded by ICS1, EDS5 and PBS3 (Rekhter et al, 2019;Torrens-Spence et al, 2019). They are all ERGs and directly regulated by TFs SARD1 and CBP60g Sun et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogen-induced SA accumulation is required for plant immunity, and one major pathway of SA biosynthesis is via isochorismate (IC) (Dempsey et al, 2011). The IC pathway involves several enzymes that are required for the key catalytic steps, and encoded by ICS1, EDS5 and PBS3 (Rekhter et al, 2019;Torrens-Spence et al, 2019). They are all ERGs and directly regulated by TFs SARD1 and CBP60g Sun et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, promoters of several genes induced by pathogens and involved in SA metabolism emerged as TPR1 bound (Figure 3). These genes include Isochorismate Synthase 1 ( ICS1 ) and avrPphB Susceptible 3 ( PBS3 ) important for isochorismate derived SA accumulation (Wildermuth et al, 2001; Rekhter et al, 2019; Torrens-Spence et al, 2019), as well as Downy Mildew Resistant 6 ( DMR6 ) encoding an SA deactivating 5-hydroxylase (Zhang et al, 2017). These observations suggest that TPR1 is directly involved in host transcriptional reprogramming of immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, jar1 mutant does not produce bioactive JA-Isoleucine and defective in JA signaling, while vas2 mutant over-accumulate free IAA at the expense of IAAglutamate [11,13]. In addition, Arabidopsis avrPphB susceptible 3 (pbs3) mutants were found to be more susceptible to bacterial pathogens because production of isochorismoyl glutamate, the precursor of salicylic acid (SA), catalyzed by PBS3, is compromised [14]. Over-expression of Arabidopsis Dwarf in Light 1 (DFL1) and Yadokari 1 (YDK1), which are induced by auxin, causes hyper-sensitivity to light treatment leading to dwar sm [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, only Group and GH3 genes have been identi ed in Gramineae genomes [23][24][25]. Using GH3 enzymes in various plant species, preferential substrates of GH3 enzymes in terms of acyl acids and amino acids have been determined [8,14,18,22,[26][27][28][29][30]. In addition, a systematic evaluation of sixty GH3 enzymes from Arabidopsis, grape, rice, Physcomitrella, and Sellaginella also revealed that not all the enzymes in Group are involved in JA signaling and twelve out of sixteen subgroup GH3 enzymes tested displayed clear substrate preferences for IAA using three acyl acid substrates -jasmonate, IAA, and 4 hydroxybenzoate (4-HBA) [31].…”
Section: Introductionmentioning
confidence: 99%